2016
DOI: 10.1371/journal.pone.0154729
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of Psychological Stress with Depressive and Anxiety Symptoms among Chinese Bladder and Renal Cancer Patients: The Mediating Role of Resilience

Abstract: BackgroundThe prevalence of depressive and anxiety symptoms and their associated factors in bladder and renal cancer patients are not well evaluated in China. Given the growing attention to positive psychological constructs in the field of oncology, it is necessary to explore the effects of these constructs on depressive and anxiety symptoms. This study aims to explore the associations of psychological stress with depressive and anxiety symptoms among Chinese bladder and renal cancer patients and the mediating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 49 publications
7
56
1
Order By: Relevance
“…The Chinese CES-D scale has been widely used in previous studies. 28 , 29 The Cronbach’s α coefficient for the CES-D scale was 0.90 in the present study.…”
Section: Methodssupporting
confidence: 53%
“…The Chinese CES-D scale has been widely used in previous studies. 28 , 29 The Cronbach’s α coefficient for the CES-D scale was 0.90 in the present study.…”
Section: Methodssupporting
confidence: 53%
“…There is some evidence that resilience is negatively related to depressive symptoms [7,8,41]. We hypothesized that there would be a negative correlation between the Chinese version of the RS-14 and the CES-DC.…”
Section: Discussionmentioning
confidence: 97%
“…The mediatorstested in our study differs from most previous studies [72, 7981], in which authors have mostly chosen self-efficacy [72], emotional abuse [79], sleep disturbances [80], and negative perception of social support [81]. Although Li [73] also suggested that resilience partially mediated the relation between psychological stress with depressive and anxiety symptoms, their research differed from ours in terms of population, dependent and independent variables, and even the resilience scale to some extent. Although we all used the Resilience Scale-14, the original scale of the Chinese revision we used is from Block J [59].…”
Section: Discussionmentioning
confidence: 99%